A STUDY OF INDIVISIBLE RESERVES IN COOPERATIVES IN EU MEMBER STATES - Mills, Cliff (International Journal of Cooperative Law, 2025)
Indivisible reserves are a common featureof cooperatives. They can help to providefinancial stability; build solidarity and sustainability for future generations; and can act as adisincentive to those seeking to take over its assets.